2008
DOI: 10.1093/ajcn/88.2.289
|View full text |Cite
|
Sign up to set email alerts
|

Food patterns and cardiovascular disease risk factors: The Swedish INTERGENE research program

Abstract: It is possible to distinguish food patterns that are related to obesity and obesity-related cardiovascular disease risk factors in contrast with a more healthy pattern conforming with current dietary guidelines. Thus, the results indicate no reason for questioning the current recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
92
1
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 46 publications
19
92
1
7
Order By: Relevance
“…The Modern pattern had high loadings of processed foods including roasted/smoked foods, instant foods, fermented fruits/ vegetables, fermented foods and soft drinks. In Western countries there is a positive association between 'Western' dietary patterns and hypertension (19)(20)(21)(22)(23) , although a null association has also been reported (24)(25)(26)(27)(28) . However, in Asia no significant association between a Western dietary pattern and hypertension was found in most existing studies (29)(30)(31)(32)(33)(34)(35)(36) , with a small number of studies showing a positive association between this pattern and hypertension (37)(38)(39)(40) .…”
Section: Modern Dietary Pattern and Hypertensionmentioning
confidence: 98%
See 1 more Smart Citation
“…The Modern pattern had high loadings of processed foods including roasted/smoked foods, instant foods, fermented fruits/ vegetables, fermented foods and soft drinks. In Western countries there is a positive association between 'Western' dietary patterns and hypertension (19)(20)(21)(22)(23) , although a null association has also been reported (24)(25)(26)(27)(28) . However, in Asia no significant association between a Western dietary pattern and hypertension was found in most existing studies (29)(30)(31)(32)(33)(34)(35)(36) , with a small number of studies showing a positive association between this pattern and hypertension (37)(38)(39)(40) .…”
Section: Modern Dietary Pattern and Hypertensionmentioning
confidence: 98%
“…In Western populations, dietary patterns rich in vegetables are associated with reduced risk of hypertension or lower levels of blood pressure (19)(20)(21)(22)(26)(27)(28) . However, in Asian populations, the association between vegetable-rich dietary patterns and hypertension or blood pressure remains uncertain.…”
Section: Prudent Pattern and Hypertensionmentioning
confidence: 99%
“…Recently, many studies have reported associations between dietary patterns and disease risks, including metabolic abnormalities, cardiovascular disease, and some cancers. [1][2][3][4] Despite some inconsistency in the findings, generally dietary patterns rich in whole grains, legumes, vegetables, and fish had favorable effects on metabolic abnormalities, 2,3 whereas western patterns, characterized by high-fat foods, increased the risk of metabolic abnormalities, such as type 2 diabetes and cardiovascular disease. [5][6][7] These studies often measured diet at a single point, so that associations between changes in dietary patterns over time and health outcomes have rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there has been a recent emphasis on research which identifies holistic dietary patterns in populations as determinants of disease (2,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) . Investigating dietary patterns better reflects the real-life scenario that foods are not consumed in isolation and allows us to look at the impact of overall diet on health.…”
mentioning
confidence: 99%